PENGARUH PERAN ORANG TUA TERHADAP PENDIDIKAN KARAKTER SISWA KELAS V SD NEGERI 067246 FLAMBOYAN RAYA MEDAN TAHUN PEMBELAJARAN 2025/2026 - Hepriana Simbolon; Dyan Wulan Sari HS; Anton Sitepu; Reflina Sinaga; Eka Margareta Sinaga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the level of parental role, the level of students’ character education, and the influence of parental role on the character education of fifth-grade students at SD Negeri 067246 Flamboyan Raya Medan in the academic year 2025/2026. This research employed a quantitative approach using a correlational method. The population consisted of 30 fifth-grade students and their parents. Data were collected using questionnaires that had met validity and reliability requirements, with Cronbach’s Alpha values of 0.801 for the Parental Role instrument and 0.799 for the Character Education instrument. Data were analyzed using normality testing, Pearson Product-Moment correlation, t-test, and coefficient of determination analysis with the assistance of SPSS version 25.0. The results showed that both parental role and students’ character education were categorized as good, with mean scores of 84.27 and 81.43, respectively. The correlation analysis revealed a positive and significant relationship between parental role and students’ character education (r = 0.527; sig. = 0.003 < 0.05). The hypothesis test showed that the calculated t-value was 3.277, which was higher than the t-table value of 2.048, indicating that the alternative hypothesis (Ha) was accepted and the null hypothesis (H₀) was rejected. The coefficient of determination indicated that parental role contributed 27.77% to students’ character education, while the remaining 72.23% was influenced by other factors. Therefore, it can be concluded that there is a positive and significant influence of parental role on the character education of fifth-grade students at SD Negeri 067246 Flamboyan Raya Medan in the academic year 2025/2026.